Spectroscopie des céramiques pour l’amélioration du rendement des cellules photovoltaïques - Bensalem, C.; Boulma, E.; Diaf, M.; Khiari, S. (University of Eloued جامعة الوادي, 2018)
This optical investigation of glass-ceramics formed by annealing glasses with compositions 50 GeO2 - 40 PbO - 10 PbF2 - x EuF3, x = [0.5; 1; 1.5; 2] and polycrystalline ceramics with composition 100 PbF2, y EuF3, with y = 5, 10, 15 and 20. For each material, the photoluminescence spectrum and the photoluminescence lifetimes of the 5D0, 5D1 and 5D2 Eu3+ levels are measured. Occurrence of β-PbF2: Eu3+ nanocrystallites in the glass-ceramics is confirmed and total ceramisation requires more than 10 % of EuF3 with respect to PbF2 in the starting glass. In the β-PbF2: Eu3+ ceramics and glass-ceramics, Eu3+ ions replace Pb2+ in their regular cubic site, but they interact together to form dimmers and higher nuclearity clusters. For the EuF3 rates investigated here, there are no isolated Eu3+ ions in the PbF2 lattice. A preliminary investigation of the optical properties of co-doped β-PbF2: Gd3+- Eu3+ ceramics was also performed. It shows that efficient Gd3+ → Eu3+ energy transfer occurs in these ceramics. The Pb2+ ions of the lattice may also be involved in the energy transfer process.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: oxyfluoride glasses, glass-ceramic, europium, fluorescence, thermal analysis, crystallisation